Penafsiran Makna Alat Bukti Sempurna Akta Notaris dalam Sudut Pandang Pembuktian - Dwipayani, Triveni Chrisna; Dananjaya, Nyoman Satyayudha (Acta Comitas, 2025)
The aim of this research is to understand and analyze notarial deeds as perfect evidence. In practice, however, the authenticity of deeds remains a subject of dispute. As perfect evidence, a notarial deed should inherently possess an ultimatum nature, be non-contestable, and the court must reject any examination of cases related to the challenge of the deed. However, in reality, deeds can still be contested or even annulled, leading to inconsistencies in the understanding of perfect evidence. This research employs a normative legal research method, which begins with issues related to the ambiguity of norms or distortions in the perfect normative value of deeds. The findings indicate that a notarial deed is considered perfect evidence and does not require additional evidence. According to Article 16, paragraph (9), a notarial deed can become a private deed if one of the requirements in paragraph (1) letter m and paragraph (7) is not fulfilled. To determine the strength of perfect evidence, interpretive methods are necessary. The author uses three interpretive methods: grammatical, systematic, and teleological. Based on systematic interpretation, a notarial deed can be considered perfect evidence when it meets both material and formal requirements. The conclusion of this research is that a notarial deed cannot be deemed perfect if it remains subject to challenge, due to the lack of material requirements within the notarial deed.